ANALYSIS OF FINANCIAL STATEMENTS FOR ASSESSING FINANCIAL PERFORMANCE OF PT INDOFOOD JAKARTA - Ambarwati, Nunik; Lastari, SE., MM, Siwi; Murdo, M.Si, Drs. Yuri (Management, 2010)
Company performance can be judged from the company´s profitability or ability to obtain profits. Profit as one measure of corporate performance is the result of complex management in terms of revenue and expenses in order to provide a favorable difference. The performance of the company can be seen from the market share, productivity, service to consumers, the image from the point of employee and contribution in the development of the country. According to Sofyan S. (1999:190) analysis of financial statements is a process to describe the posts report into smaller units of information and see the relationship that is significant or meaningful with each other between the quantitative data as well as nonquantitative data in order to determine the condition more finance in a very important role in the decision making process. From the quick ratio analysis showed that in 2002 the company is not liquid, whereas in 2003 and in 2004 the company´s liquid. Return on total asset size in 2002 to 2004 companies in poor condition, while the analysis in terms of return on equity in 2002 and 2003 the company but in 2004 both companies in poor conditionFrom the analysis of operating performance, in 2002 to 2004 companies in the running of their business is not good, because from 2002 to 2004 the profits from the company´s decline. Keywords: corporate performance, profits, quick ratio, return on total assets, operating performance analysis